PERAN KADER JUMANTIK DENGAN KEJADIAN PENYAKIT DBD DI WILAYAH KERJA PUSKESMAS BANJAREJO - Novita Duwiyanti; Avicena Sakufa Marsanti; Zaenal Abidin (Jurnal Delima Harapan, 2022)
Mosquito larva monitoring officers are one of the team worksestablished by a community in each neighborhood unit/community unit (RT/RW) to perform a Periodic Larvae Inspectionand Monitoring, as well as Aedes aegypti andAedes albopictus Mosquito Nest Eradication (PSN). Mosquitos aedes aegypti a cause dengue faver. Based on secondary data from the Banajarejo Health Center, there were 2 cases of dengue fever in 2021 and in 2022 there were 11 cases, the increase in cases could be influenced by several factors, such as humans and the environment. This study aims to determine the relationship of larva monitoring interpreters (jumantik) with the incidence of dengue disease in cadres in the working area of the Banjarejo Health Center. This study uses a quantitative method with a cross sectional approach. The number of samples in this study were 136 respondents, the sampling technique in this study was proportional random sampling. Collecting data using a questionnaire that was analyzed by chi-square test by looking at the relationship between the independent variable and the dependent variable. The results of this study indicate that there is a relationship between the role of larvae monitoring interpreters and the incidence of dengue disease in cadres in the working area of the Banjarejo Health Center, the p-value = 0.032 with value RP (95% CI) = 5,817(1,228-28,551). The conclusion of this study is that there is a relationship between jumantik cadres and the incidence of dengue disease in cadres in the working area of the Banjarejo Health Center. For further researchers, it is recommended to add other factors to the incidence of DHF, such as human behavior factors and environmental factors as well.